IDENTIFICATION OF SCIENTIFIC REASONING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS - Wulandari, Etrica Damayanti; Efwinda, Shelly; Hakim, Abdul; Syam, Muliati; Damayanti, Puardmi (Universitas Labuhanbatu, 2025)
Purpose – This study aims to 1) identify the level of scientific reasoning ability and 2) the difference between indicators of scientific reasoning ability of male and female junior high school students in Samarinda on climate change.Methodology – The research method used is descriptive quantitative, with data collection techniques through tests in the form of multiple-choice questions with reasons totaling 11 questions that have been validated and tested for reliability. The subjects of this study were class VII students, totaling 86 students from 3 junior high schools in Samarinda. The instrument used was a scientific reasoning test consisting of 6 indicators: conservation reasoning, correlation reasoning, variable control, probabilistic reasoning, proportional reasoning, and deductive hypothesis.Findings – The results showed that 1) The scientific reasoning ability of junior high school students in Samarinda averaged 45.63 in the transition stage between concrete and formal operations. Each indicator is in a different category: good, sufficient, and deficient. The highest result on the conservation reasoning indicator (65.33) shows that students adequately retain their knowledge, even though the appearance of the object changes. The lowest result on deductive hypothesis reasoning (35.08) shows that students cannot make conclusions on a problem. 2) There is no significant difference between male and female students in scientific reasoning ability related to climate change material in all junior high schools in Samarinda.Contribution – This study provides recommendations for innovative learning methods, such as problem-based learning, to improve the scientific reasoning skills of male and female students.